Gender Differentials in Self-Esteem of Adolescents with Selfie Addiction - Kaur, Satinder; Vig, Deepika (International Journal of Bio-resource and Stress Management, 2023)
An investigation was planned during the year 2016 to observe the effect of selfie addiction on self-esteem across two genders and locales. The data was collected from 360 rural and urban school going adolescents (studying in 10th 11th and 12th grades) using Self-Structured Selfie Addiction Checklist consisting of three levels: borderline (0–4 scores), acute (5–9 score) and chronic (10–14 scores) in addition to Self-Esteem Inventory to assess three levels of self-esteem. The study was conducted in schools of Ludhiana District, India in the year 2017. The results showed that in the case of borderline selfie addiction, a larger proportion of girls in comparison to boys had low self-esteem, while higher number of boys in contrast to girls demonstrated a high level of self-esteem. At the acute and chronic levels of selfie addiction, no gender differences were discovered. This shows that boys in comparison to girls had higher self-esteem. Moreover, across all three levels of selfie addiction, urban boys exhibited higher self-esteem than urban girls, although no significant gender differences were found in rural adolescents. The findings showed that boys had better mean scores of self-esteem than girls.